Guidance for chronic subdural hematoma surgery in the novel coronavirus pandemic (Covid-19) - Valença, Marcelo Moraes; Valença, Martina Falcão; Martins, Carolina; Andrade-Valença, Luciana Patrízia Alves; Valença, Marcelo Andrade; Silva, Ana Cristina Veiga; Azevedo Filho, Hildo Rocha Cirne de (Avanços em Medicina, 2025)
Of great concern to the neurosurgical community is this novel coronavirus pandemic 2019, a result of dissemination to all continents of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Without proper care, there is a very high chance of being infected by the lethal SARS-CoV-2 during a routine neurosurgical procedure. SARS-CoV-2 infected a significant part of the healthcare workers, including neurosurgeons, responsible for direct care for patients with Covid-19, and several of those infected have already died. Drastic modifications should be made in the process the operating room is prepared, and in the attitudes taken by medical personnel in an attempt to minimize a possible contact of the SARS-CoV-2. The novel coronavirus is present not only in the respiratory tract, but the virus may also be encountered in blood, stool, and CSF. In this article, the authors want to address the topic of how the neurosurgeons can mitigate the chance of being infected with SARS-CoV-2 during a surgical procedure performed on a patient with Covid-19. For this, we chose a common condition in neurosurgery practice - and one of the simplest in its execution - the chronic subdural hematoma (CSDH). There is still no consensus on how to operate patients with CSDH. This article aimed to elaborate a protocol with effective and minimally invasive techniques to be performed in the patient with both CSDH and Covid-19, with the dual intention of protecting the surgeon from SARS-CoV-2 infection and optimizing the patient's chance of healing.